Price-level dispersion versus inflation-rate dispersion: Evidence from three countries - David Fielding; Christopher Hajzler; James MacGee (Bank of Canada, 2017)
Inflation can affect both the dispersion of commodity-specific price levels across locations (relative price variability, RPV) and the dispersion of inflation rates (relative inflation variability, RIV). Some menu-cost models and models of consumer search suggest that the RIV-inflation relationship could differ from the RPV-inflation relationship. However, most empirical studies examine only RIV, finding that RIV is high when inflation is high. We examine city-level retail price data from Japan, Canada and Nigeria, and find that the impact of inflation on RIV differs from its effect on RPV. In particular, positive inflation shocks reduce RPV but raise RIV.
Keywords: E31; E50; 330; Inflation and prices